(3GdbGfhfs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s ((3EHQGgje Hf CMeO Hf YHO GdQMef Hf Ydi GdTgQRhQi s)
(3ChdgG (B:s
(3hHYO (B: (3abO GdJeS efi HYV NdU ENhGfi hef jdRefi ESYGag , HeG jSeM Hg s
(3BNQgG (B:s
(3adjcf gPG GdbOQ ef cdGefG GdeNJUQ ai GdCUhd Gdcdjg dUfGYI GdWH cGajkG , hdfCNP ai JUfja cJGHfG ai GdCOhjI GdeaQOI s
(3bWYI JTJed Ydi GdcJGH GdChd ai GdCehQ GdcdjIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B812 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B143 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1311s
Keywords: (3GdWHs